Will sexual robots modify human relationships? A psychological approach to reframe the symbolic argument. (3rd May 2021) - Bisconti, Piercosma
ABSTRACT: The purpose of this paper is to understand if and how interactions with Sexual Robots will modify users' relational abilities in human-human relations. We first underline that, in today's scholar discussion on the 'symbolic argument', there is no theoretical framework explaining the process of symbolic shift between human-robot interactions (HRI) and human-human interactions (HHI). To clarify the symbolic shift mechanism, we propose the concept of objectual mediation. Moreover, under the lens of Winnicott's object-relation theory, we argue that HRI can structurally modify users relationality, degrading intersubjective abilities: Sexual Robots may blurry the limit between the 'internal object' and the external one. We conclude that, under certain conditions, interactions with Sexual Robots may bring the user back to an infantile object-relation setting, worsening the user ability to manage relational frustration. This will negatively impact on human-human interactions and social values in general.